Synthesis and Polymerization of Poly Acryl Imide and One of Their Derivatives Then Curing the Product with Alkyl Halide - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
The present work involved four steps: First step include reaction of acrylamide ,N-?-Methylen-bis(acryl amide) and N-tert Butyl acryl amide with poly acryloyl chloride in the presence of triethyl amine (Et3N) as catalyst, the second step include homopolymerization of all products of the first step by using benzoyl peroxide(BPO) as initiator in (80-90)Co in the presence of Nitrogen gas(N2). In the third step the poly acrylimide which prepare in second step was convert into potassium salt by using alcoholic potassium hydroxide solution. Fourth step include Alkylation of the prepared polymeric salts in third step by react it with different alkyl halides(benzyl chloride, allylbromide , methyl iodide) by using DMF as solvent for(10-12) hours. Structure Confirmation of all prepared polymers were proved using FT-IR, 1H-NMR and C13-NMR spectroscopy for some polymers. Other physical properties including softening and melting points of the polymers were also measured.